(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article examines the emergence of new conservative youth in contemporary Peru, situating them in continuity and contrast with previous traditions of youth mobilization linked to the left, social protest, and political radicalization. Drawing on an exploratory qualitative study, it analyzes university-based collectives that, through intensive use of social media, digital formats, and political training programs, have articulated themselves with conservative right-wing party projects. The central argument is that this politicization is not a spontaneous or merely reactive phenomenon but a deliberate process of organization that acts as a hinge between social movements and institutional politics. The Peruvian case confirms the relevance of emotions, cultural repertoires, and communicational devices in building youth political communities but introduces a novelty: the consolidation of an organized conservative youth seeking to dispute cultural hegemony and project leadership into institutional arenas, with significant implications for democracy